Measuring the impact of malaria infection on indicators of iron and vitamin A status: a systematic literature review and meta-analysis. Issue 1 (14th January 2023) - Sandalinas, Fanny; Filteau, Suzanne; Joy, Edward J. M.; Segovia de la Revilla, Lucia; MacDougall, Amy; Hopkins, Heidi
Abstract: Inflammation and infections such as malaria affect estimates of micronutrient status. Medline, Embase, Web of Science, Scopus and the Cochrane library were searched to identify studies reporting mean concentrations of ferritin, hepcidin, retinol or retinol binding protein in individuals with asymptomatic or clinical malaria and healthy controls. Study quality was assessed using the US National Institute of Health tool. Random effects meta-analyses were used to generate summary mean differences. In total, forty-four studies were included. Mean ferritin concentrations were elevated by: 28·2 µg/l (95 % CI 15·6, 40·9) in children with asymptomatic malaria; 28·5 µg/l (95 % CI 8·1, 48·8) in adults with asymptomatic malaria; and 366 µg/l (95 % CI 162, 570) in children with clinical malaria compared with individuals without malaria infection. Mean hepcidin concentrations were elevated by 1·52 nmol/l (95 % CI 0·92, 2·11) in children with asymptomatic malaria. Mean retinol concentrations were reduced by: 0·11 µmol/l (95 % CI −0·22, −0·01) in children with asymptomatic malaria; 0·43 µmol/l (95 % CI −0·71, −0·16) in children with clinical malaria and 0·73 µmol/l (95 % CI −1·11, −0·36) in adults with clinical malaria. Most of these results were stable in sensitivity analyses. In children with clinical malaria and pregnant women, difference in ferritin concentrations were greater in areas with higher transmission intensity. We conclude that biomarkers of iron and vitamin A status should be statistically adjusted for malaria and the severity of infection. Several studies analysing asymptomatic infections reported elevated ferritin concentrations without noticeable elevation of inflammation markers, indicating a need to adjust for malaria status in addition to inflammation adjustments.